Effect of disaster preparedness training towards knowledge of COVID-19 among rural society in Banjararum Village, Kulon Progo Regency, Yogyakarta - Sutono Sutono; Bayu Fandhi Achmad (Journal of Community Empowerment for Health, 2021)
The number of COVID-19 daily cases in Indonesia reached a record high in 2021, and the prevalence of active cases increased beyond hospital capacity. Disaster preparedness training involving the key role of society is substantial to stop the spread of COVID-19. This study aimed to determine the effect of disaster preparedness training towards the knowledge of COVID-19 pandemic among rural society. The intervention involved 29 participants, who were located in a rural area of the Special Region of Yogyakarta Province. Participants were required to complete the pre-test and post-test to determine the effect of disaster preparedness training on participant knowledge. There was a significant effect of disaster preparedness training on public knowledge about COVID-19 (P <0.005). There was an increase in the mean score between pre-test (9.93) and post-test (11.68). By increasing society’s knowledge, the society can play a maximum role in COVID-19 prevention and control measures.